The Vietnam War a documentary reader - Miller, Edward Garvey (Chichester, West Sussex, United Kingdom WILEY Blackwell, 2016)
The Vietnam War is an outstanding collection of primary documents related to America s conflict in Vietnam which includes a balance of original American and Vietnamese perspectives, providing a uniquely varied range of insights into both American and Vietnamese experiences -- Provided by the publisher.
Colonialism, nationalism and communism -- The first Indochina war and the origins of American involvement -- The two Vietnams -- The rise of the Viet Cong -- The fall of Diem -- Escalation -- On the battlefield -- The Tet offensive -- Home fronts -- Pacification, Vietnamization and fighting while negotiating -- Victory and defeat -- Memories and legacies.
Includes index.
Keywords: Vietnam War, 1961-1975. -- Sources